2018
DOI: 10.1088/1742-6596/1022/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomathematics elements in Batik Bali using backpropagation method

Abstract: Abstract. Batik is one of traditional arts that has been established by the UNESCO as Indonesia's cultural heritage. Batik has varieties and motifs, and each motifs has its own uniqueness but seems similar, that makes it difficult to identify. This study aims to develop an application that can identify typical batik Bali with etnomatematics elements on it. Etnomatematics is a study that shows relation between culture and mathematics concepts. Etnomatematics in Batik Bali is more to geometrical concept in line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
2
0
3
Order By: Relevance
“…Furthermore, there are several ethnics which implemented of Ethnomathematics in their life in Cipatujah, West Java, for example, they apply the traditional mathematical concept in the way they determine the time to sail for fishing, and the way they construct their houses (Kusuma, Dewanto, Ruchjana, & Abdullah, 2017). The motifs of batik are an Ethnomathematics context related to lines, angles, triangles, quadrilaterals, circles, and transformation geometry, which exist in several cultures in Indonesia (Risdiyanti & Prahmana, 2018;Lestari, Irawan, Rahayu, & Parwati, 2018;Pramudita & Rosnawati, 2019;Irawan, Lestari, Rahayu, & Wulan, 2019). However, few researchers have explored mathematical modeling in Yogyakarta's literature.…”
mentioning
confidence: 99%
“…Furthermore, there are several ethnics which implemented of Ethnomathematics in their life in Cipatujah, West Java, for example, they apply the traditional mathematical concept in the way they determine the time to sail for fishing, and the way they construct their houses (Kusuma, Dewanto, Ruchjana, & Abdullah, 2017). The motifs of batik are an Ethnomathematics context related to lines, angles, triangles, quadrilaterals, circles, and transformation geometry, which exist in several cultures in Indonesia (Risdiyanti & Prahmana, 2018;Lestari, Irawan, Rahayu, & Parwati, 2018;Pramudita & Rosnawati, 2019;Irawan, Lestari, Rahayu, & Wulan, 2019). However, few researchers have explored mathematical modeling in Yogyakarta's literature.…”
mentioning
confidence: 99%
“…Several studies about ethnomathematics have been carried out on several types of batik in different locations in Indonesia. such as the research conducted by Arwanto (2017) on the typical Cirebon Trusmi batik, which shows that in Cirebon Cirebon batik contains mathematical elements, including geometric concepts of symmetry, transformation (reflection, translation, and rotation), and congruence.While Lestari, et al (2018) in their research results show thatethnomathematics in Batik Bali is more to geometrical concept in line of strong Balinese culture element. Tresnadi, et al (2015) findings suggest that the values found in Indonesian batik ornaments in the Nitiki game clearly show thepatterns of how traditional culture of batik survives and thrives in Indonesian society, as well asshow the flexibility of batik against the current development of modern culture, including itsintegration as culture-based content in interactive media.Therefore, the researcher wants to show how the results of ethnomathematics exploration in Jember batik and what mathematical concepts are contained in the batik motifs that are made and reveal the philosophical value contained therein.…”
Section: Introductionmentioning
confidence: 87%
“…Beberapa penelitian tentang etnomatematika menjadi topik menarik diantaranya penggunaan motif batik berkaitan dengan garis, sudut, segitiga, segiempat, lingkaran, dan geometri transformasi berdasarkan kebudayaan di Indonesia (Risdiyanti, et. al, 2019;Lestari, et. al., 2018;Irawan, et.…”
Section: Sampai Pada Tahun 1985 Terbentuklah Organisasi the Internati...unclassified